Life hardships and its relationship with Suicide Probability among University Students - Al Dosari, Sarah Saud; Al-Maizer, Hind Aqeel (Journal of Humanities & Social Sciences, 2017)
This study aimed to identify the major Events of Life hardships among King Saud university students, and its relationship with Suicide Probability. The study was based on Social Survey Methodology with a Simple Random Sampling Method, and used both measures of Suicide Probability and life hardships. It was applied to 377 students enrolled in the first year’s joint study at King Saud University in Riyadh for the academic year 1437- 1438. The results showed that the average rate of the sample members that agreed that they suffered from life hardships is 17.75% , While the average rate of the sample members who didn’t agree with suffering from any life hardships is 82.25%. The results also showed that the responses’ total average of the sample members, on all scales, was 2.02 with verbal estimate (Sometimes). As for the dimensions of the scale, the first rank was negative self- evaluation with an average of 2.45, then the hopelessness with an average of 2.19, with verbal estimate (Sometimes). While the suicide perception dimension had an average of 1.74, and the dimension of hostility had an average of 1.71, with verbal estimate (rarely). The results also revealed that there is no statistically significant relationship at the level 0.05 between the sample members’ responses on the bound total of Life hardships and responses on the bound total of the Suicide Probability, as well as the dimensions: (feeling of hopelessness, negative self- esteem, hostility), while there is a statistically significant relationship between responses on the Life hardships scale and the perception of suicide dimension. In the view of the findings, lots of recommendations is given to improve the student services to reduce the hardships which is facing the college student.